Papercrete as infill materials for composite wall system - Mohammed B.S. (EuroJournals, Inc., 2023)
A composite wall system (CWS) made of cement bonded wood particles panels are fabricated from wood-construction waste particles and Portland cement; to be infilled with a lightweight material (papercrete) to overcome the poor acoustic and thermal properties and also to enhance its fire resistance and screw withdrawal force. The papercrete has been proved to have better thermal conductivity and sound absorption and sound transmission if compared with conventional construction materials and also it found to enhance the fire resistance of the CWS to 2 hours fire rated. EuroJournals Publishing, Inc. 2009.